Foreign Direct Investment Trend in Nepal and Recent Changes in Bylaws to Reduce Administrative Hurdles (Voice of Teacher, 2021)
Foreign Direct Investment is one of the major source of external finance for the economic growth and development of a country, specially the Least Developed Countries (LDC’s) like Nepal. Inflow of FDI is very low in Nepal in comparison to its neighboring countries. In this paper comparative analysis of FDI inflow in Nepal and in SAARC countries and administrative hurdles in importing FDI in Nepal has been analyzed to come to the conclusion.This study is based on the secondary data of FDI inflow in recent five years, acts, rules, regulations, and bylaws regarding FDI and their recent improvements. In the past, investment climate in Nepal was not favorable to the foreign investors and FDI inflow was very low. Amendment and change in laws and regulation to simplify administrative procedures has created good investment climate in Nepal and being favorable to foreign investors. We can expect that FDI will increase remarkably in the days to come.